IMPLEMENTASI CASHLESS SEBAGAI UPAYA PENCEGAHAN PUNGUTAN LIAR (PUNGLI) DI LEMBAGA PEMASYARAKATAN KELAS IIA SRAGEN - Prakosa, Afredo Dian; Santoso, Iman (Universitas Wiralodra, 2024)
This research aims to evaluate the implementation of a cashless system as an effort to prevent illegal levies (pungli) at the Class IIA Correctional Institution (Lapas) in Sragen. Through a descriptive qualitative approach, this research analyzes how the cashless system is implemented, the obstacles faced, and its impact on preventing illegal levies. Data was collected through in-depth interviews with prison officers, inmates, and direct observation of the transaction process. The research results show that the implementation of a cashless system at Class IIA Sragen Prison has been effective in reducing the potential for illegal levies. However, there are several obstacles that need to be considered, such as the limited knowledge of inmates regarding the cashless system and technical issues related to the facilities. Overall, the cashless system has great potential to enhance transparency and accountability in financial management within the prison environment. This research suggests the need for continuous efforts in providing education to inmates and officers, as well as improving supporting infrastructure for the optimization of the cashless system.